Studies of the Carbohydrates Content in Tissues of Hamster (Mesocricetus Auratus) Infected with Hookworm (Ancylostoma Ceylanicum) (International Journal of Preventive Medicine and Health (IJPMH), 2024)
Hookworm infections are the helminthic infection that affects tropical and subtropical areas. Several laboratory animals have been infected with hookworms. Due to parasitic infection, the structure and function of tissues undergo severe derangements and metabolic disorders. In the present study, a hamster, Mesocricetus auratus was infected with a hookworm, Ancylostoma ceylanicum. Investigation of the Carbohydrate content of A.ceylanicum in M. auratus was studied in control and infected ones. Understanding the level of pathogenicity caused by an A. ceylanicum infection can be aided by examining the total amount of carbohydrates present in the tissues of the host, M. auratus. A biochemical estimation of the total carbohydrate content was made. The brain and spleen were found to have higher carbohydrate contents. There was decreased carbohydrate activity in the kidney, liver, gut, and muscle. The present study depicted the alterations in the total carbohydrate content in various tissues of the host, M. auratus due to the infection of A. ceylanicum. The result of the data obtained in the various tissues due to infection was found to be statistically significant. It was further plotted graphically plotted and interpreted. The research work done in the present study helped to understand the biochemical changes taking place in the host, Mesocricetus auratus due to hookworm, Ancylostoma ceylanicum infection.